Biochemical profiling and antioxidant evaluation of Martynia annua and Polygonum viviparum: investigating hepatoprotective properties against abiotic stress: Medicinal properties of M. annua and P. viviparum - E-Habiba, Umm; Qureshi, Zahid Habib; Farooq, Bakhtawar; Jabeen, Raheela; Kazmi, Mahwish Batool; Qammar, Najma; Rafi Qamar; Hafiz Muhammad Rashad Javeed; Shahzad, Muhammad; Albalawi, Mody; Mohammed Ali Al-Duais; Hayam A. Alwabsi; et al. (Cellular and Molecular Biology, 2025)
The liver is the second largest organ in the body, playing a crucial role in maintaining homeostasis and regulating metabolism. However, the prevalence of liver diseases has been rising steadily due to an increase in both infectious and non-infectious factors. Medicinal plants offer a remarkable opportunity to enhance our healthcare system by addressing various diseases through their ability to control oxidative stress and support metabolic processes. This revision improves readability while retaining the original meaning. In the present study, purified methanol extracts of Martynia annua and Polygonum viviparum at different concentrations were used to explore the antioxidant and hepatoprotective potential against abiotic stress on liver cells. Firstly total flavonoids and total phenolic contents of both plants were measured and then their antioxidant activities were determined through DPPH radical scavenging activity and FRAP assay. Moreover, bioactive compounds and in vitro hepatoprotective potential among these plants were determined through LC-MS and Liver Slice Culture assay respectively. In P. viviparum high amounts of TPC and TFC were observed with maximum antioxidant potential in terms of DPPH inhibition at 84% and high ferric-reducing ability at 240 mg/mL. The presence of different phytoconstituents like Myricetin, Gallic acid, Ferulic acid, Chlorogenic acid, Sweroside, Morroniside, Echonoside, Swertiamarin and Protocatechuic acid were confirmed in M. annua and P. viviparum in LC-MS study. The maximum hepatoprotective potential in terms of minimum cytotoxicity 6% and 9% were observed in M. annua and P. viviparum respectively. It was revealed that both plants have stunning hepatoprotective properties to prevent liver from toxicants and their related complications due to high antioxidant potential and active metabolites.